Safety and Effectiveness of Eculizumab throughout Three Pregnancies in a Patient with Refractory Generalized Myasthenia Gravis: A Case Report - Khalil, Nadia; Guerra Hernandez, Claudia; Farias, Jerrica; Murray, Kathleen; Suresh, Niraja; Gooch, Clifton; Vu, Tuan H. (Case reports in neurology, 2025)
We describe maternal and fetal outcomes in a patient who had three successful pregnancies while being treated with eculizumab for AChR+ gMG. This is a follow-up to our previously published report describing outcomes with this C5 complement inhibitor during the patient’s first pregnancy. Eculizumab conferred adequate gMG disease control during these pregnancies, although there were instances of increased gMG symptoms during the first trimester and postpartum period without requirement for rescue therapy. The patient experienced disseminated gonococcal infection once during her second pregnancy, a serious adverse event that was likely related to complement inhibition by eculizumab. The patient additionally experienced two nonserious and treatment responsive yeast infections. There were no negative outcomes reported with any of the pregnancies in fetal, neonatal, or infantile periods. In the context of the existing literature, this report provides additional insight on potential outcomes with use of eculizumab in patients with gMG. While the report suggests favorable effectiveness and fetal outcomes, it also highlights potential for adverse events, namely, maternal infections. Additional reports on clinical outcomes in pregnancy in patients with gMG are needed to guide risk-benefit stratification for eculizumab.